Les violences sexuelles commises par des soldats allemands et leur répression dans le Calvados, de l’Occupation à la Bataille de Normandie (juin 1940-août 1944) - Charlotte Barnabé (Genre & Histoire)
Although there is now a growing body of work on sexual violence committed during the Second World War, this study focuses on the issues at stake at the level of the department, despite the limited number of sources available. Calvados presents a particular context, with a very dense occupation from June 1940 to June 1944, which was brutally interrupted by the Allied landing on 6 June 1944 and three months of close fighting for the liberation of the territory. Under the effect of this resumed fighting, the relatively similar opportunistic rapes during the Occupation were followed by more numerous, more violent and more localised attacks in the summer of 1944. How did the local authorities deal with this when the perpetrator was German and the victim French? Collaboration in terms of investigation seems to have been very limited in the context of German predominance. The occupying authority was then free to severely condemn the soldiers guilty of rape, in accordance with its military regulations and the injunction to carry out a « korrekt » occupation. Here again, the effect of the fighting led to condemnations appearing less formal and more violent. Thus, this study addresses the way in which the military context influences sexual violence committed by soldiers and how it was handled by an army that was successively an occupying force and then fighting.